RIGHTS OF INDIVIDUALS AND OBLIGATIONS OF THE STATE IN PROTECTING AIR QUALITY - Drenovak-Ivanović, Mirjana M. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The basis for the development of institutes in the field of air quality protection, recognised by present environmental law, originates back in Roman law. At the end of the first half of the 3rd century, we come across a closer division of entities indicated by Marcian, who, starting from the potential to use entities, singles out, as a special category, entities used by all people and which cannot be the subject of private property (res communes omnium). The first entities considered to be naturally common to all were air and water. In the 21st century, impaired air quality had been identified by the World Health Organization as a major cause of the increasing number of cases of premature death globally. The author points out that although Serbia is a signatory to the basic international agreements which set the framework for the protection of air quality, the Protocols and amendments to the Protocols to the Convention on Long-range Transboundary Air Pollution adopted after 2012 have not been ratified. As the envisaged rules are mostly part of the environmental acquis, it is likely that the rules envisaged by the non-ratified Protocols and accompanying amendments will become part of the domestic legal framework in the process of harmonisation of Serbian law with EU law. Further to the analysis of Member States’ basic obligations it the application of Directive 2008/50/EC on Ambient Air Quality and Cleaner Air for Europe, the author singles out the most important cases of the CJEU practice which point to the criteria for assessing whether Member States apply adequate measures that lead to reduction of emissions prescribed by the directive. The analyses show that individuals have active legal standing in administrative disputes initiated against the inaction of the competent authorities, meaning that the competent authority did not adopt the Air Protection Action Plan as an answer to exceeding values of emission levels prescribed by Directive 2008/50/EC. The author goes on to present the measures for domestic courts which would ensure the shortest possible period of emissions above limit values in such cases. In addressing the degree of harmonisation of our law with international standards and EU law in the field of air quality protection, the concluding statements point to the recommendations and opinions of the Protector of Citizens, forming the basis for amending the positive law.